PHARMACOGNOSTIC EVALUATION OF ABIES WEBBIANA LEAF: A SIDDHA HERBAL INGREDIENT - Rajalakshmi P; V, Vadivel; N, Ravichandran; V, Sudha; P, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To evaluate the therapeutic potential of Abies webbiana (Wall ex D. Don) Lindl, plants leaves belongs to Pinaceae family are grown in Northern India, Afghanistan, China (Tibet), Nepal, and Pakistan. It is a large tree grows up to 50 m height. Leaves of this plant are useful in Siddha and Ayurveda Systems of Medicine. It acts as an expectorant, carminative, stomachic, and tonic. It is the main ingredient in the Siddha formulations such as Thalisathi choornam and Thalisadi vadagam, which are used for respiratory problems such as cold, cough, wheezing, tuberculosis, indigestion, loss of appetite, and vatha diseases. Methods: In this study, we have investigated the phytochemical profile, pharmacognostic characters, and gas chromatography-mass spectrometry (GC-MS) compounds of methanolic extract of A. webbiana leaves. Results: Phytochemical screening showed the presence of steroids, terpenes, sugars, phenols, flavonoids, tannins, saponins, and quinones. The leaf material revealed loss on drying (6.90%), total ash (5.23%), acid-insoluble ash (0.57%), water-soluble extractive (23.79%), alcohol-soluble extractive (18.37%), and pH was 5.25. 29 compounds were detected in GC-MS analysis and benzenepropanol, 4-hydroxy-Ã -methyl, 2-furancarboxaldehyde, and 5-(hydroxymethyl) are the predominant components. Conclusions: This study provides the pharmacognostic standards of A. webbiana leaf for their authentication and utilization in herbal medicine. Keywords: Abies webbiana, Pharmacognosy, Phytochemicals, Gas chromatography-mass spectrometry, Herbal medicine.